Monitoring and benchmarking population diet quality globally: a step‐wise approach. (17th September 2013) - Vandevijvere, S.; Monteiro, C.; Krebs‐Smith, S. M.; Lee, A.; Swinburn, B.; Kelly, B.; Neal, B.; Snowdon, W.; Sacks, G.; ,
Summary: INFORMAS (International Network for Food and Obesity/non‐communicable diseases Research, Monitoring and Action Support) aims to monitor and benchmark the healthiness of food environments globally. In order to assess the impact of food environments on population diets, it is necessary to monitor population diet quality between countries and over time. This paper reviews existing data sources suitable for monitoring population diet quality, and assesses their strengths and limitations. A step‐wise framework is then proposed for monitoring population diet quality. Food balance sheets (FBaS), household budget and expenditure surveys (HBES) and food intake surveys are all suitable methods for assessing population diet quality. In the proposed 'minimal' approach, national trends of food and energy availability can be explored using FBaS. In the 'expanded' and 'optimal' approaches, the dietary share of ultra‐processed products is measured as an indicator of energy‐dense, nutrient‐poor diets using HBES and food intake surveys, respectively. In addition, it is proposed that pre‐defined diet quality indices are used to score diets, and some of those have been designed for application within all three monitoring approaches. However, in order to enhance the value of global efforts to monitor diet quality, data collection methods and diet quality indicators need further development work.